(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
The study sought to investigate whether the social development of the young adults (in the form of resilience) is more closely related to single parents or the upbringing of both parents and how the nonappearance of 1 of the 2 parentages can affect these imperative aspects. Young adults from sole mother or father and intact households, both 320 boys and girls, 160 young adults from broken setups, and 160 young adults from happy families were selected through a convenient sampling technique from different educational institutes. This study adopted the quantitative research design and method of the survey to gather information. The structured Resilience Scale (RS) was used to gather data. A noteworthy variance was seen in young adults ‘resilience with single and both parents. There was a significant difference found between age, and resilience and even between education and resilience. There was no important change visible in the order of birth between young adults with both parents, and single parents. The results have a major impact on clinicians and educators working with families who are concerned with nurturing positive, emotionally close-step relationships as well as maintaining sturdy matrimonial ties and beliefs among spouses in marriages.